Evolocumab: rising momentum as novel antidyslipidemic drug - Mehani, Rekha; Shukla, Ajay; Yadav, V. K.; Sahu, Rimjhim (International Journal of Basic & Clinical Pharmacology, 2017)
Increased levels of low density lipoprotein cholesterol are responsible for the major cardiovascular events. Low density lipoprotein cholesterol reduction has proved to be highly effective in reducing the risk of major cardiovascular (CV) events in various trials. ACC/AHA guidelines recommend lipid-lowering therapy for patients with known cardiovascular diseases (CVD). Statins are the gold standard treatment for all types hypercholeterolemia but still there is need of some other lipid-lowering therapies especially in patients with statin intolerance and in patients responding inadequately to statins. Proprotein convertase subtilisin/kexin type 9 (PCSK9) was discovered in 2003 and subsequently emerged as a novel target for LDLC-lowering therapy. Evolocumab is a fully human monoclonal immunoglobulin G2 (IgG2) directed against human PCSK9. Evolocumab binds to PCSK9 enzyme rendering it unable to bind to the LDLR. More LDLR are available to bind to LDLC. Evolocumab increase the density of LDLR on the surface of hepatocytes, thereby increasing the uptake of LDL particles and decreasing the LDLC in the blood. Evolocumab has proved its efficacy with LDLC reduction from 53% to 75% and associated with minor side effects. Evolocumab has corroborated its effectiveness in reduction in the levels of LDLC. This drug has shown efficacy in heterozygous and homozygous subtypes of familial hypercholesterolemia. Statin intolerance seen in about 15% of all patients restricts the use of first line drug for dyslipidemia. Evolocumab can be a useful option in statin intolerant patients and in patients responding inadequately to statins.